THE CONTRIBUTION OF ISLAMIC EDUCATION TO RELIGIOUS THINKING ACTIVISTS OF ISLAMIC STUDENT ACTIVITIES UNIT AND ITS IMPLICATIONS ON RADICALISM IN HIGHER EDUCATION - Irfandi, Irfandi; Syahidin, Syahidin; Fakhruddin, Agus (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Islamic education essentially provides space for reason to be able to develop human potential. Islamic Religious Education in PAI Lectures in tertiary institutions has a function besides strengthening student Islam, it also builds a peaceful, moderate and tolerant diversity. Based on the theory of the psychology of religion, mature religious people are adherents of religions that are peaceful, moderate and tolerant. The understanding of the contribution of PAI lectures as well as the style of Islamic religious thinking is of course different. In general, this study aims to describe the contribution of PAI to the religious way of thinking of Islamic UKM activist students and its implications for the notion of radicalism in Indonesian University of Education Universities. The participant who will be the source of the research is the head of the Islamic UKM. The object of his research is the opinion of the head of the Islamic UKM regarding the contribution of PAI and religious thinking. Data collection techniques using observation, interviews, documentation. It appears that most Islamic UKM activists at the Indonesian University of Education think moderately and inclusively. Understanding of Islamic law is quite widespread so that the impetus towards radicalism is very small